Control and ownership of assets within rural Ethiopian households - Fafchamps, Marcel; Quisumbing, Agnes R. (International Food Policy Research Institute, 2001)
This paper investigates how the control and devolution of productive assets are allocated among husband and wife. Using detailed household data from rural Ethiopia, the authors show that assets brought to marriage, ownership of assets, control within marriage, and disposition upon death or divorce are only partly related.